The Patient Dignity Inventory: A Novel Way of Measuring Dignity-Related Distress in Palliative Care - Chochinov, H.; Hassard, T.; McClement, S.; Hack, T.; Kristjanson, Linda; Harlos, M.; Sinclair, S.; Murray, A. (Elsevier, 2008)
Quality palliative care depends on a deep understanding of distress facing patients nearing death. Yet, many aspects of psychosocial, existential and spiritual distress are often overlooked. The aim of this study was to test a novel psychometric—the Patient Dignity Inventory (PDI)—designed to measure various sources of dignity-related distress among patients nearing the end of life. Using standard instrument development techniques, this study examined the face validity, internal consistency, test–retest reliability, factor structure and concurrent validity of the PDI. The 25-items of the PDI derive from a model of dignity in the terminally ill. To establish its basic psychometric properties, the PDI was administered to 253 patients receiving palliative care, along with other measures addressing issues identified within the Dignity Model in the Terminally Ill. Cronbach's coefficient alpha for the PDI was 0.93; the test–retest reliability was r = 0.85. Factor analysis resulted in a five-factor solution; factor labels include Symptom Distress, Existential Distress, Dependency, Peace of Mind, and Social Support, accounting for 58% of the overall variance. Evidence for concurrent validity was reported by way of significant associations between PDI factors and concurrent measures of distress. The PDI is a valid and reliable new instrument, which could assist clinicians to routinely detect end-of-life dignity-related distress. Identifying these sources of distress is a critical step toward understanding human suffering and should help clinicians deliver quality, dignity-conserving end-of-life care.